2012
DOI: 10.1007/s13191-012-0221-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Maxillary and Mandibular Anterior Teeth Width with the Length of Index and Little Finger

Abstract: The maxillary anterior teeth width can be calculated with the formula (1.130 × index finger length - 11.972), mandibular anterior teeth width can be calculated with the formula (1.006 × little finger length - 2.231).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Toward this end, the size and form of the maxillary anterior teeth are important not only to dental esthetics, but also to facial esthetics. The goal is to have the maxillary anterior teeth restore optimal dento-labial relations in harmony with the overall facial appearance (Ahila et al 2014). As observed in this study, the mean of intercanthal distance and intercanine width was 30.75 and 34.56mm, respectively.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Toward this end, the size and form of the maxillary anterior teeth are important not only to dental esthetics, but also to facial esthetics. The goal is to have the maxillary anterior teeth restore optimal dento-labial relations in harmony with the overall facial appearance (Ahila et al 2014). As observed in this study, the mean of intercanthal distance and intercanine width was 30.75 and 34.56mm, respectively.…”
Section: Discussionsupporting
confidence: 60%
“…Facial attractiveness is a factor in many important social interactions. A number of studies have found that facial attractiveness is related to how humans perceive others (Ahila et al 2014). The development of new dental materials and techniques has led to a greater number of treatment options that maximize the likelihood of an attractive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The shape of the anterior teeth is considered one of the most important factor for the evaluation of facial esthetics. 3 4 The determinants of anterior teeth esthetics can be classified as gingival and tooth-related, 5 and these can be divided further by the shape and color of each tooth, width ratio relative to the adjacent tooth, and other factors. The maxillary anterior mesiodistal width ratios play an important role in the formation of a balanced dentition.…”
Section: Introductionmentioning
confidence: 99%
“…A harmonious smile is an important component of facial aesthetics 1 and one of the main considerations among patients seeking dental treatment 2 . However, what can be considered harmonic according to a specific culture or person may not be right for another, and may affect social interactions 2 .…”
Section: Introductionmentioning
confidence: 99%
“…An important factor contributing to a harmonious dentition is size, shape and arrangement of maxillary central incisors seen from the front 5 . Different techniques have been proposed to optimize the harmonious shape of maxillary anterior teeth 1,[4][5][6][7][8] . These are based on the work of Levin, who introduced the golden ratio in dental aesthetics 9 .…”
Section: Introductionmentioning
confidence: 99%